Strong oxygen release type perovskite oxygen carrier material and preparation method thereof

By doping Co in the perovskite oxygen carrier, regulating its structure and performance, a strong oxygen-release perovskite oxygen carrier was developed, which solved the problem of low oxygen release in the existing oxygen carrier and achieved efficient oxygen decoupling performance and fuel conversion rate.

CN119898823AInactive Publication Date: 2025-04-29CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510078842.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing oxygen decoupled oxygen carriers have problems with low oxygen release and slow kinetic speed in chemical chain combustion technology, resulting in unburned gases at the outlet of the fuel reactor, affecting the energy conversion efficiency and cost.

Method used

A strong oxygen-release perovskite oxygen carrier material is developed, with the general formula of CaMnxCo1-xO3-δ, which regulates its lattice oxygen transport performance and mechanical stability through Co doping to achieve short-term rapid oxygen release.

Benefits of technology

The oxygen decoupling performance is significantly improved, the oxygen release amount and oxygen release rate are significantly increased, which is higher than the oxygen release amount of most oxygen decoupling oxygen carriers, and has good cycle stability, which can effectively convert the fuel gas reaction path and improve the fuel conversion rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898823A_ABST
    Figure CN119898823A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical looping combustion, and particularly discloses a strong oxygen release type perovskite oxygen carrier material and a preparation method thereof, the oxygen carrier has a general formula of CaMnxCo1-xO3-delta (x = 0.85-1), and the preparation method comprises the following preparation steps: (1) mixing nitrate of Ca, Mn and Co elements with a complexing agent and a solvent to obtain a precursor solution; and (2) heating and stirring the precursor solution, carrying out air drying and uniform grinding, carrying out high-temperature calcination, and cooling to room temperature to obtain the perovskite oxygen carrier powder. The preparation process is simple and easy to operate, the prepared perovskite oxygen carrier has excellent oxygen decoupling performance, the oxygen release rate and the oxygen release amount are both higher than those of an existing chemical looping oxygen decoupling oxygen carrier at present, and a feasible scheme is provided for improving the fuel gas conversion rate and achieving efficient development of the chemical looping combustion technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical looping combustion, and specifically relates to a strong oxygen-releasing perovskite oxygen carrier material and a preparation method thereof. Background Art

[0002] As a new combustion technology, chemical chaining combustion can achieve automatic enrichment of CO2 during fuel conversion and reduce the energy consumption of CO2 separation. It is the lowest-cost carbon capture technology currently. Chemical chaining combustion technology splits the overall fuel conversion reaction into two steps that occur in different reactors, using oxygen carriers as the medium for lattice oxygen transfer and heat transfer, avoiding direct contact between air and fuel in space, and preventing flue gas pollutants and CO2 from being diluted by N2 in the air during the reaction, thereby achieving product separation, source pollutant suppression and cascade utilization of energy. Oxygen carriers and reactors are the core of the chemical chain combustion system. Low-valent oxygen carriers are oxidized by O2 in the air in the air reactor to generate high-valent oxygen carriers, accompanied by the release of a large amount of heat and the generation of oxygen-deficient air. The high-valent oxygen carriers are reduced to low-valent oxygen carriers by the fuel in the fuel reactor and generate H2O and CO2. After condensation of the exhaust gas at the outlet of the fuel reactor, high-purity CO2 can be obtained for subsequent utilization and storage. This continuous cycle can achieve flameless combustion with self-separation of CO2. The overall reaction in the reactor is consistent with the traditional direct combustion reaction of air.

[0003] The reactor system in the chemical chain combustion system provides a place for the fuel to react with the oxygen carrier. The fuel reactor is dominated by typical gas-solid reactions. From a thermodynamic point of view, theoretically, the oxygen carrier can achieve complete conversion of the fuel gas so that only CO2 and H2O are present at the outlet of the fuel reactor. However, in actual operation, it is common that the fuel gas cannot be fully converted. At present, the oxygen demand fraction of the incompletely converted gas is mostly 5-30%, resulting in a decrease in the energy ladder conversion efficiency and an increase in the oxygen supplementation cost. The fuel gas concentration and the solid content of the oxygen carrier in the fuel reactor riser decrease rapidly with height, which limits the kinetic rate of the reduction reaction between the fuel gas and the oxygen carrier. This gas-solid reaction defect is the fundamental reason for the presence of unburned gas at the outlet of the fuel reactor. Therefore, in the case of being unable to change the inevitable trend of the reduction of the fuel gas concentration, the chemical chain combustion of solid fuels represented by coal requires oxygen carriers with fast kinetic speed and high reaction activity. At present, there are more than 1,200 types of oxygen carriers reported internationally. Some oxygen carriers with oxygen decoupling ability at high temperature (such as Cu-based, Mn-based, and Co-based) can decompose and release gaseous O2 in an oxygen-deficient environment, converting the coke and volatile matter produced by the pyrolysis of solid fuels into CO2 and H2O by combustion, and the reaction path of some fuel gases is changed from gas-solid reaction to gas-gas reaction, thereby improving its conversion rate. However, the oxygen carriers with oxygen decoupling characteristics currently have problems that limit their application, such as: the rapid oxygen release temperature of Cu-based oxygen carriers is relatively high (above 950°C), but they are prone to high-temperature sintering; Mn-based oxygen carriers are cheap and efficient but easy to wear and cannot be reused for a long time. At the same time, they are difficult to be rapidly oxidized in air reactors due to thermodynamic limitations; Co-based oxygen carriers are expensive and environmentally unfriendly, and are not recommended for large-scale application.

[0004] In recent years, artificially synthesized oxygen carriers with perovskite structure have attracted wide attention due to their high reactivity, stable structure and low particle wear rate. The general molecular formula of perovskite oxygen carrier is ABO 3-δ , where the A position is an alkaline earth or rare earth metal cation with a larger atomic radius, the B position is a transition metal cation with a smaller atomic radius, and δ is an oxygen ion vacancy that can change with the state of the perovskite. Compared with other conventional metal oxide oxygen carriers, the A and B positions of perovskite oxygen carriers can be replaced by metal ions with similar radii to achieve regulation of crystal structure and reaction characteristics, and the changes in the internal structure of the crystal during the redox reaction are reversible, and the basic framework structure can be maintained unchanged. Therefore, for perovskite oxygen carriers with oxygen decoupling ability, the introduction of dopants at the A or B position can selectively enhance their lattice oxygen transport performance and mechanical stability. The rapid release of a large amount of oxygen in a short period of time can break the gas-solid reaction kinetics limitations of the fuel gas in the reactor, which is beneficial to enhance the conversion of reducing gases. According to the type of main element at the A position, the perovskite oxygen carriers that have been studied and can be applied to the chemical chaining combustion process mainly include three types: Ca series, La series, and Sr series, such as Cax La 1-x Mn 1-y M y O 3-δ (M=Mg,Ti,Fe,or Cu),LaNi 0.5 Co 0.5 O 3-δ ,Sr(Fe 1-x Cu x ) 3-δ However, the oxygen release amount is generally lower than 1wt%, making it difficult to achieve the transformation of the reducing gas reaction pathway from gas-solid reaction to gas-gas reaction.

[0005] Therefore, in order to improve the conversion rate of unburned gases in the fuel reactor, it is crucial to develop a perovskite oxygen carrier with strong oxygen release capacity that can be applied to the chemical looping combustion process. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of existing oxygen-decoupled oxygen carriers and to provide a strong oxygen-releasing perovskite oxygen carrier material and a preparation method thereof. The preparation process is simple and the prepared oxygen carrier can achieve a large amount of oxygen release in a short time, providing a feasible solution to the problem of unburned gas conversion in chemical chain combustion technology.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A strong oxygen-releasing perovskite oxygen carrier material, wherein the oxygen carrier is a Co-doped Ca-Mn-based perovskite oxygen carrier with a general formula of CaMn x Co 1-x O 3-δ , x=0.85~1.

[0009] A method for preparing the above-mentioned strong oxygen-releasing perovskite oxygen carrier material, the method comprising:

[0010] Step 1: adding calcium nitrate, manganese nitrate, cobalt nitrate, a complexing agent and a solvent into a glass container according to the molar ratio of Ca, Mn and Co elements to prepare a precursor solution;

[0011] Step 2: The precursor solution is heated and stirred to form a uniform gel, and then air-dried, uniformly ground, and calcined at high temperature to obtain perovskite oxygen carrier powder. In this step, controlling the heating temperature and stirring time can accelerate the complexation and form high-quality gel materials; drying is to remove the solvent and volatile substances in the system, and further realize the transformation of gel into solid material; calcination is the key step to complete the chemical transformation and structure formation of the material, which determines the properties and performance of the final material.

[0012] Furthermore, in step 1, the molar ratio of the Ca, Mn and Co elements is 1:0.85 to 1:0 to 0.15.

[0013] Furthermore, in step 1, the molar ratio of the total metal cations contained in the calcium nitrate, manganese nitrate and cobalt nitrate to the complexing agent is 1:1-2.

[0014] Furthermore, in step 1, the complexing agent is citric acid and ethylene glycol, and the solvent is deionized water. There is no requirement for the amount of the solvent as long as it can dissolve other solutes.

[0015] Furthermore, in step 2, the heating and stirring temperature is 70-80° C. and the time is 4-6 hours.

[0016] Furthermore, in step 2, the drying temperature is 110-120° C. and the drying time is 24-40 hours.

[0017] Furthermore, in step 2, the high-temperature calcination is carried out in a muffle furnace or a tubular furnace under an air atmosphere.

[0018] Furthermore, in step 2, the calcination treatment includes a pre-combustion stage with a temperature of 300°C and a calcination time of 30 minutes and a high-temperature calcination stage with a temperature of 900°C and a calcination time of 8 hours, and the heating rate is 3-4°C / min.

[0019] Compared with the prior art, the present invention has the following advantages and outstanding effects:

[0020] 1. The present invention constructs a Co-doped Ca-Mn-based perovskite oxygen carrier for chemical looping combustion process, and realizes the regulation of the performance of the perovskite oxygen carrier by adjusting the Co doping ratio. Compared with the undoped state, the oxygen decoupling performance of the Co-doped Ca-Mn-based perovskite oxygen carrier at high temperature is greatly improved, which is manifested as a significant increase in the oxygen release amount and oxygen release rate, which is higher than the oxygen release amount of most current oxygen decoupling oxygen carriers (<1%). At the same time, it also has good cycle stability. A small amount of the perovskite oxygen carrier can be used to convert the fuel gas reaction path, thereby improving the fuel conversion rate.

[0021] 2. The method for preparing the Co-doped Ca-Mn-based perovskite oxygen carrier adopted in the present invention has a simple process, significant effect, easy operation, and easy large-scale production to save costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the mass change of the perovskite oxygen carriers with different Co doping amounts in the thermogravimetric analyzer in an oxygen release-oxidation cycle experiment at 700° C.;

[0023] Figure 2It is a graph of oxygen release rates of perovskite oxygen carriers with different Co doping amounts described in Examples 1 to 5 of the present invention and Comparative Example 1 at 700° C. on a thermogravimetric analyzer;

[0024] Figure 3 This is a graph showing the mass change of the perovskite oxygen carrier described in Example 2 of the present invention in an oxygen release-oxidation cycle experiment at 650-900° C. on a thermogravimetric analyzer;

[0025] Figure 4 This is a graph of oxygen release rates of the perovskite oxygen carrier described in Example 2 of the present invention at different temperatures (650-900° C.) on a thermogravimetric analyzer. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] Embodiment 1:

[0028] First, according to the molar ratio of metal elements Ca: Mn: Co = 1: 0.97: 0.03, 8.4g Ca(NO3)2·4H2O, 17.0g Mn(NO3)2·4H2O, and 0.3g Co(NO3)2·6H2O were weighed and dissolved in an appropriate amount of deionized water, and then 14.0g anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1: 1, and 4.5g ethylene glycol was weighed and added to the solution according to the molar ratio of 1: 1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, CaMn was obtained. 0.97 Co 0.03 O 3-δ Perovskite oxygen carrier powder.

[0029] In this system, the function of ethylene glycol is mainly as an auxiliary complexing agent, which works together with citric acid to further stabilize metal ions and prevent aggregation and precipitation. Although it has dissolving ability, it is not the main solvent. It mainly promotes the complexation and gelation process by changing the viscosity of the solution and providing a hydroxyl chemical environment.

[0030] Embodiment 2:

[0031] First, according to the molar ratio of metal elements Ca: Mn: Co = 1: 0.95: 0.05, 5.0g Ca(NO3)2·4H2O, 10.0g Mn(NO3)2·4H2O, and 0.3g Co(NO3)2·6H2O were weighed and dissolved in an appropriate amount of deionized water, and then 8.5g of anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1: 1, and 2.5g of ethylene glycol was weighed and added to the solution according to the molar ratio of 1: 1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, CaMn was obtained. 0.95 Co 0.05 O 3-δ Perovskite oxygen carrier powder.

[0032] Embodiment 3:

[0033] First, according to the molar ratio of metal elements Ca: Mn: Co = 1: 0.92: 0.08, 8.4g Ca(NO3)2·4H2O, 16.1g Mn(NO3)2·4H2O, and 0.83g Co(NO3)2·6H2O were weighed and dissolved in an appropriate amount of deionized water, and then 14.0g of anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1: 1, and 4.5g of ethylene glycol was weighed and added to the solution according to the molar ratio of 1: 1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, CaMn was obtained. 0.92 Co 0.08 O 3-δ Perovskite oxygen carrier powder.

[0034] Embodiment 4:

[0035] First, according to the molar ratio of metal elements Ca: Mn: Co = 1: 0.88: 0.12, 8.4g Ca(NO3)2·4H2O, 15.5g Mn(NO3)2·4H2O, and 1.25g Co(NO3)2·6H2O were weighed and dissolved in an appropriate amount of deionized water, and then 14.0g anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1: 1, and 4.5g ethylene glycol was weighed and added to the solution according to the molar ratio of 1: 1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, CaMn was obtained. 0.88 Co 0.12 O 3-δ Perovskite oxygen carrier powder.

[0036] Embodiment 5:

[0037] First, according to the molar ratio of metal elements Ca: Mn: Co = 1: 0.85: 0.15, 5.0g Ca(NO3)2·4H2O, 9.0g Mn(NO3)2·4H2O, and 0.95g Co(NO3)2·6H2O were weighed and dissolved in an appropriate amount of deionized water, and then 8.5g of anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1: 1, and 2.5g of ethylene glycol was weighed and added to the solution according to the molar ratio of 1: 1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, CaMn was obtained. 0.85 Co 0.15 O 3-δ Perovskite oxygen carrier powder.

[0038] Comparative Example 1:

[0039] First, according to the molar ratio of metal elements Ca:Mn=1:1, 8.4g Ca(NO3)2·4H2O and 17.5g Mn(NO3)2·4H2O were weighed and dissolved in an appropriate amount of deionized water, and then 14.0g anhydrous citric acid was added according to the molar ratio of the complexing agent to the metal ions in the nitrate of 1:1, and 4.5g ethylene glycol was weighed and added to the solution according to the molar ratio of 1:1 with citric acid. The precursor solution after mixing was stirred at 80°C for 5h to obtain a wet gel, and the wet gel was placed in an oven at a constant temperature of 120°C and dried for 24h to generate a dry gel, which was then transferred to a muffle furnace and pre-burned at 300°C for 30min in an air atmosphere, and then burned at 900°C for 8h. After the furnace temperature was naturally cooled and uniformly ground, the CaMnO3 perovskite oxygen carrier powder was obtained.

[0040] Performance Test:

[0041] The oxygen decoupling performance of the perovskite oxygen carrier prepared in the above Examples 1 to 5 and Comparative Example 1 was evaluated as follows.

[0042] 1. Comparison of oxygen release rate and oxygen release amount of perovskite oxygen carriers with different Co doping amounts:

[0043] The test was conducted on a thermogravimetric analyzer. 10 mg of each of the six perovskite oxygen carriers prepared above was placed in an alumina crucible, and then the crucible was placed on the thermogravimetric analyzer balance for an oxygen release-oxidation cycle test. The test temperature was 700°C, the heating rate was 20°C / min, the total gas flow rate was constant at 120 ml / min, the atmosphere in the oxygen release stage was N2, which lasted for 30 minutes, and the atmosphere in the oxidation stage was air, which lasted for 30 minutes. The total duration of the cycle test was about 240 minutes. The mass change curve of the oxygen carrier in the oxygen release-oxidation cycle is shown in the figure below. Figure 1 As shown in Figure 2, the oxygen release rate of oxygen carriers with different Co doping amounts is as follows: Figure 2 Table 1 shows the oxygen release of oxygen carriers with different Co doping amounts. The results show that under the same working conditions, compared with CaMnO3 without Co doping, the oxygen decoupling performance of all Co-doped Ca-Mn-based perovskite oxygen carriers is improved, especially CaMn 0.95 Co 0.05 O 3-δ The oxygen release rate is significantly increased by 2 times, and the oxygen release amount is increased from 0.15-0.16wt% to 0.33-0.34wt%, indicating that the perovskite oxygen carrier has excellent oxygen decoupling performance.

[0044] Table 1700℃ perovskite CaMn x Co 1-x O 3-δ (x=0.85~1) oxygen release

[0045] Oxygen carrier Oxygen release (wt%) <![CDATA[CaMnO3]]> 0.15~0.16 <![CDATA[CaMn 0.97 What 0.03 O 3-δ ]]> 0.27~0.30 <![CDATA[CaMn 0.95 What 0.05 O 3-δ ]]> 0.33~0.34 <![CDATA[CaMn 0.92 What 0.08 O 3-δ ]]> 0.25~0.27 <![CDATA[CaMn 0.88 What 0.12 O 3-δ ]]> 0.18~0.19 <![CDATA[CaMn 0.85 What 0.15 O 3-δ ]]> 0.18~0.19

[0046] 2. Comparison of oxygen decoupling performance of perovskite oxygen carriers at different temperatures

[0047] According to the experimental results of oxygen release-oxidation cycle of perovskite oxygen carriers with different Co doping amounts, the perovskite oxygen carrier CaMn 0.95 Co 0.05 O 3-δ Oxygen release-oxidation cycle tests were carried out at different temperatures on a thermogravimetric analyzer. The test temperatures were 650°C, 700°C, 750°C, 800°C, 850°C, and 900°C, the heating rate was 20°C / min, the total gas flow rate was constant at 120ml / min, the atmosphere in the oxygen release stage was N2, which lasted for 30 minutes, and the atmosphere in the oxidation stage was air, which lasted for 30 minutes. The total cycle test duration was about 240 minutes. The mass change curve of the oxygen carrier in the oxygen release-oxidation cycle is shown in Figure 2. Figure 3 As shown in the figure, the oxygen release rate of the oxygen carrier at different temperatures is as follows Figure 4 As shown in Table 2, the oxygen release of the oxygen carrier at different temperatures. The results show that the perovskite oxygen carrier CaMn 0.95 Co 0.05 O 3-δ The oxygen release rate and oxygen release amount increase significantly with the increase of temperature. When the temperature increases from 650°C to 900°C, the oxygen release rate increases by about 10 times, and the oxygen release amount increases from 0.19-0.20wt% to 1.5-2.8wt%, indicating that the perovskite oxygen carrier has a strong oxygen decoupling ability, which exceeds the oxygen release of most current oxygen decoupling oxygen carriers (<1wt%), providing feasibility for changing the conversion path of unburned gas.

[0048] Table 2 Perovskite CaMn at different temperatures 0.95 Co 0.05 O 3-δ Oxygen release

[0049]

[0050]

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A strong oxygen-releasing perovskite oxygen carrier material, characterized in that: The oxygen carrier is a Co-doped Ca-Mn-based perovskite oxygen carrier, the general formula of which is CaMn x Co 1-x O 3-δ , x=0.85~1.

2. A method for preparing a strong oxygen-releasing perovskite oxygen carrier material as claimed in claim 1, characterized in that: The method is: Step 1: adding calcium nitrate, manganese nitrate, cobalt nitrate, a complexing agent and a solvent into a container according to the molar ratio of Ca, Mn and Co elements to prepare a precursor solution; Step 2: The precursor solution is heated and stirred to form a uniform gel, and then air-dried, uniformly ground, and calcined at a high temperature to obtain a perovskite oxygen carrier powder.

3. The preparation method according to claim 2, characterized in that: In step 1, the molar ratio of the Ca, Mn and Co elements is 1:0.85 to 1:0 to 0.

15.

4. The preparation method according to claim 2, characterized in that: In step 1, the molar ratio of the total metal cations contained in the calcium nitrate, manganese nitrate and cobalt nitrate to the complexing agent is 1:1-2.

5. The preparation method according to claim 2, characterized in that: In step 1, the complexing agents are citric acid and ethylene glycol, and the solvent is deionized water. There is no requirement for the amount of the solvent, as long as it can dissolve other solutes.

6. The preparation method according to claim 2, characterized in that: In step 2, the heating and stirring temperature is 70-80° C. and the time is 4-6 hours.

7. The preparation method according to claim 2, characterized in that: In step 2, the drying temperature is 110-120° C. and the drying time is 24-40 hours.

8. The preparation method according to claim 2, characterized in that: In step 2, the high-temperature calcination is carried out in an air atmosphere using a muffle furnace or a tubular furnace.

9. The preparation method according to claim 2, characterized in that: In step 2, the calcination treatment includes a pre-combustion stage with a temperature of 300° C. and a calcination time of 30 minutes and a high-temperature calcination stage with a temperature of 900° C. and a calcination time of 8 hours, and the heating rate is 3-4° C. / min.

Citation Information

Patent Citations

  • Perovskite oxidation catalyst

    JP1989270944A

  • OXIDE COMPOUND MATERIAL HAVING n-TYPE THERMOELECTRIC CHARACTERISTIC

    JP2009117449A

  • Complex oxide

    JP2022102787A